2015
DOI: 10.1152/japplphysiol.00703.2014
|View full text |Cite
|
Sign up to set email alerts
|

Significant mechanical interactions at physiological lengths and relative positions of rat plantar flexors

Abstract: In situ studies involving supraphysiological muscle lengths and relative positions have shown that connective tissue linkages connecting adjacent muscles can transmit substantial forces, but the physiological significance is still subject to debate. The present study investigates effects of such epimuscular myofascial force transmission in the rat calf muscles. Unlike previous approaches, we quantified the mechanical interaction between the soleus (SO) and the lateral gastrocnemius and plantaris complex (LG+PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 67 publications
2
47
1
Order By: Relevance
“…The second pathway contains branches of the popliteal artery and tibial nerve running from the popliteal fossa to the proximal-dorsal surface of LG and MG muscle bellies. In situ, mechanical interaction between SO and LG of the rat has been reported (Bernabei et al, 2015) for a range of MTU length changes (6 mm), which were consistent with the ones estimated in this study (7.2 and 6.4 mm for LG and SO, respectively; Fig. 6A).…”
Section: Mechanical Consequences Of Displacements Between Neighboringsupporting
confidence: 91%
See 2 more Smart Citations
“…The second pathway contains branches of the popliteal artery and tibial nerve running from the popliteal fossa to the proximal-dorsal surface of LG and MG muscle bellies. In situ, mechanical interaction between SO and LG of the rat has been reported (Bernabei et al, 2015) for a range of MTU length changes (6 mm), which were consistent with the ones estimated in this study (7.2 and 6.4 mm for LG and SO, respectively; Fig. 6A).…”
Section: Mechanical Consequences Of Displacements Between Neighboringsupporting
confidence: 91%
“…6A). However, in the study by Bernabei et al (2015), both muscles were maximally activated, while the extent of mechanical interaction has been shown to decrease with submaximal activation and passive muscle conditions (Tijs et al, 2015a(Tijs et al, , 2016a. Moreover, the maximal MTU relative displacement imposed in the study by Bernabei et al LG proximal tendon is detached from its origin on the lateral epicondyle of the femur to show the intermuscular connective tissues and SO muscle belly lying more anterior in the triceps surae compartment.…”
Section: Mechanical Consequences Of Displacements Between Neighboringmentioning
confidence: 87%
See 1 more Smart Citation
“…This may be advantageous for accurate control of ankle joint stability. This seems to be in contrast to a recent study showing that lengthening gastrocnemius and plantaris muscles proximally, simulating knee extension, increased the force exerted at the distal tendon of soleus muscle significantly (Bernabei et al, 2015). However, because ankle plantar-flexors have largely comparable lines of action (Tijs et al, 2014), the presence of myofascial force transmission will not affect the functional output at the joint.…”
Section: Functional Implicationscontrasting
confidence: 82%
“…Although tissue deformations indicate effects of myofascial force transmission, the applied imaging techniques cannot provide a direct measure of the mechanical effects at the tendon or joint. A study that did assess the mechanical effect at the tendon reported sizable epimuscular myofascial force transmission between active rat ankle plantarflexor muscles for a physiological range of muscle lengths and relative muscle positions (Bernabei et al, 2015). In contrast, ankle moments exerted by soleus muscle in rats (Tijs et al, 2015a) and cats (Maas and Sandercock, 2008) were not affected by length changes of passive synergists, as imposed by changes in knee angle.…”
Section: Introductionmentioning
confidence: 99%